2013
DOI: 10.1016/j.enpol.2012.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Customer value of smart metering: Explorative evidence from a choice-based conjoint study in Switzerland

Abstract: Implementing smart metering is an important field for energy policy to successfully meet energy efficiency targets. From an integrated social acceptance and customerperceived value theory perspective we model the importance of customer value of smart metering in this regard. We further shape the model on a choice-based conjoint experiment with Swiss private electricity customers. The study finds that overall customers perceive a positive value from smart metering and are willing to pay for it. Further, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 38 publications
(59 reference statements)
4
34
0
9
Order By: Relevance
“…Realising the potential that the residential sector holds for energy savings may be compromised if aspects of consumer value and acceptance are disregarded (Kaufmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Realising the potential that the residential sector holds for energy savings may be compromised if aspects of consumer value and acceptance are disregarded (Kaufmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DR products and services must be aligned with consumer value perception. In an exploratory study, Kaufmann et al (2013) showed how individuals with heterogeneous value perceptions could be organised in four clusters: 'risk-averse', 'technology minded', 'price sensitive' and 'safety oriented'. Table 2 below shows the resulting range of product and service offerings that result from such segmentation.…”
Section: Consumer Segmentationmentioning
confidence: 99%
“…Effective business models should cope with the consequent large customer segmentation offering more flexible and tailored solutions than in traditional energy-related business models. Based on the presented literature review, three main determinants related to customer socio-demographic aspects are selected: willingness to pay (Kaufmann et al, 2013;Sagebiel et al, 2014); customer awareness (Curtius et al, 2012;Kaufmann et al, 2013;Tabi et al, 2014); and building ownership (Sagebiel et al, 2014;Ebers and Wüstenhagen, 2015). These three determinants are explored hereafter.…”
Section: Determinants Selectionmentioning
confidence: 99%
“…Three different customer segments have been identified: The Supporters, including customers across all ages strongly supporting smart grids; The Ambiguous, characterized mainly by young customers willing to support smart grid diffusion but also concerned by data security issues; and The Skeptical, including mainly older customers not particularly concerned by environmental problems and expecting small benefits from smart grid. Kaufmann et al (2013) investigated the preference for smart metering of private consumers in Switzerland. Using conjoint analysis they assessed, on the one hand, the overall willingness of customers to pay for smart meters and, on the other hand, the existence of four customer segments with significantly different value perception: the risk averse, including customers not convinced on the benefit from smart meters; the technology minded, including customers perceiving a high value from smart metering; the price sensitive, including customers strongly concerned by the price and interested to reduce their costs with smart meters; and the safety oriented, including customers attracted by the values offered by smart meters associated with home security.…”
Section: Determinants Selectionmentioning
confidence: 99%
See 1 more Smart Citation